2001
DOI: 10.1177/104973230101100607
|View full text |Cite
|
Sign up to set email alerts
|

Tell Me What you Mean by “Sí”: Perceptions of Quality of Prenatal Care among Immigrant Latina Women

Abstract: Individual perceptions form the basis of many health research reports related to access, utilization, continuity, and quality. Many health care providers are not well equipped for designing studies or collecting data with immigrant populations. In this article, the authors examine issues in data collection on topics related to perceptions of quality of prenatal care among immigrant Latino populations. The conceptual model is Donabedian's framework for quality. Two instruments--a qualitative interview with phot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(23 citation statements)
references
References 23 publications
0
22
1
Order By: Relevance
“…Barrera and Castro (2006) reported that information gathering is a main adaptation step, and investigators can resort to concurrent activities such as reviewing literature, conducting surveys, and qualitative research to inform the content of the needed adaptation. Other experts have referred to this general process as “transcreation” (Bender, Harbour, Thorp, & Morris, 2001; Quinn, Hauser, Bell-Ellison, Rodriguez, & Frias, 2006; Solomon et al, 2005) and cultural sensitivity approach (Dutta, 2007). …”
Section: Discussionmentioning
confidence: 99%
“…Barrera and Castro (2006) reported that information gathering is a main adaptation step, and investigators can resort to concurrent activities such as reviewing literature, conducting surveys, and qualitative research to inform the content of the needed adaptation. Other experts have referred to this general process as “transcreation” (Bender, Harbour, Thorp, & Morris, 2001; Quinn, Hauser, Bell-Ellison, Rodriguez, & Frias, 2006; Solomon et al, 2005) and cultural sensitivity approach (Dutta, 2007). …”
Section: Discussionmentioning
confidence: 99%
“…This methodological approach is particularly useful when study participants and researchers come from different cultural backgrounds (19). We showed participants photocopied images of mobility aids and of elderly persons of various races using them, and asked for their opinion about the devices, and/or a story about the persons in the photos and how they were feeling about themselves and their device use.…”
Section: Data Collectionmentioning
confidence: 99%
“…1992), a method of cultural exploration, the hallmark of which is participant observation; ethology (Bottorff & Morse 1994, Bottorff et al. 1995), an approach ‘used to identify complex behavioural patterns though systematic observation’ (p. 54); Donabedian's theory of quality (Bender et al. 2001); and Parse's methodology (Kruse 1999).…”
Section: Research To Promote Understandingmentioning
confidence: 99%